The osteo-hepatic axis: a review of bone disease, insulin-like growth factor-1, and fracture risk in fatty liver disease - Dhanavade, Sushant S.; Kshirsagar, Mandakini S.; Vani, Axita C. (International Journal of Research in Medical Sciences, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD) and alcoholic fatty liver disease (AFLD) represent emerging global health burdens with significant extra-hepatic complications. Among these, metabolic bone disease, particularly osteoporosis, has gained recognition as a major determinant of patient morbidity and quality of life. This narrative review synthesizes current evidence on the pathophysiological interplay between fatty liver diseases and bone health, with special emphasis on insulin-like growth factor-1 (IGF-1) dysregulation and bone mineral metabolism. The liver serves as the primary source of circulating IGF-1 and is crucial for vitamin D metabolism. In MASLD and AFLD, hepatocellular injury leads to IGF-1 deficiency, which impairs osteoblast function and bone formation. Concurrently, vitamin D deficiency and secondary hyperparathyroidism promote increased bone resorption. Chronic inflammation, characterized by elevated cytokines like TNF-α and IL-6, further exacerbates bone loss through the RANKL/OPG pathway. In AFLD, additional direct toxic effects of alcohol on osteoblasts compound the problem. Clinical studies consistently demonstrate reduced bone mineral density and increased fracture risk in these populations. Despite this evidence, standardized screening protocols and management guidelines for bone disease in non-cirrhotic fatty liver disease patients are lacking. This review highlights the critical need for integrated care models that address both hepatic and skeletal health, advocating for routine bone density assessment in MASLD/AFLD clinics. Future research should focus on comparative studies between MASLD and AFLD, exploration of IGF-1 as a dual biomarker, and development of targeted therapeutic strategies to mitigate fracture risk in this vulnerable and growing patient population.